What to do With Wake-Up Stroke. (July 2015) - Rubin, Mark N.; Barrett, Kevin M.
Wake-up stroke, defined as the situation where a patient awakens with stroke symptoms that were not present prior to falling asleep, represents roughly 1 in 5 acute ischemic strokes and remains a therapeutic dilemma. Patients with wake-up stroke were excluded from most ischemic stroke treatment trials and are often not eligible for acute reperfusion therapy in clinical practice, leading to poor outcomes. Studies of neuroimaging with standard noncontrast computed tomography (CT), magnetic resonance imaging (MRI), and multimodal perfusion-based CT and MRI suggest wake-up stroke may occur shortly before awakening and may assist in selecting patients for acute reperfusion therapies. Pilot studies of wake-up stroke treatment based on these neuroimaging features are promising but have limited generalizability. Ongoing randomized treatment trials using neuroimaging-based patient selection may identify a subset of patients with wake-up stroke that can safely benefit from acute reperfusion therapies.